Review—Multifunctional Technology with Monolithic Integrated THz-, Photonic- and μ-Fluidic Modules. (12th April 2016) - Mai, A.; Lischke, S.; Wietstruck, M.; Zimmermann, L.; Kaynak, M.; Tillack, B.
Abstract : The purpose of this work is to review requirements and challenges for the monolithic integration of different devices and modules in a baseline CMOS-process with the intention to create a multifunctional technology platform. We consider integrated modules like THz devices, i.e. complementary SiGe heterojunction bipolar transistors, silicon photonics components in particular Ge-PIN photo detectors and the wafer-level integration of micro-fluidic channels for sensor applications. However, the monolithic integration of devices and modules for novel functionalities is still a trade-off. On the one side there are requirements of the integration concept and therefore to the process steps of the dedicated module to achieve a maximum device performance. On the other side there are influences of the process steps for the module integration to the performance of the devices from the underlying baseline technology like bipolar- and CMOS-transistors or passive components. Both aspects have to be considered to enable the co-integration of new modules in order to get a technology platform for high performances and novel functionalities. We review process adaptations of the baseline technologies to enable an efficient co-integration of different modules. Moreover we discuss critical process steps with a certain thermal budget and their influence to device performances. Finally we give recommendations for process sequences to enable a wafer level co-integration of microfluidic channels into a SiGe-BiCMOS technology platform.